Portrait: Talal Asad - Asad, Talal (Religion and society, 2020)
Autobiographical Reflections on Anthropology and Religion, Talal Asad For Talal, Jonathan Boyarin On Anthropology as Translation, Nadia Fadil Friendship and Time in the Work of Talal Asad, Hussein Ali Agrama Talal Asad’s Challenge to Religious Studies, Donovan O. Schaefer Finding Talal Asad in and beyond Buddhist Studies: Agency and Race in Modern Pasts, Ananda Abeysekara